2016
DOI: 10.1590/1519-6984.03515
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization effects on the composition and structure of macrophytes communities in a lotic ecosystem of Pernambuco State, Brazil

Abstract: Population growth in urban areas changes freshwater ecosystems, and this can have consequences for macrophyte communities as can be seen in the municipalities that border the Capibaribe River, Pernambuco, Brazil. This study reports the effects of urbanization on the composition and structure of macrophyte communities in areas along that river. The following urbanized and non-urbanized sampling sites were chosen: Sites 1 and 2 (municipality of Santa Cruz do Capibaribe), Sites 3 and 4 (municipality of Toritama),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…3) have significantly colonized the lagoon's surroundings. The presence of these species in flooded environments has also been verified in other studies (Barros 2009;Xavier et al 2016;Rodrigues et al 2017). They are related to the anthropic disturbance that has been occurring in the flooded areas over the years and to characteristics such as propagule pressure, strong adaptation to low water depth, large seed production and resistance to environmental adversities (Havel et al 2015).…”
Section: Exotic Species In Lagoa Do São Bentosupporting
confidence: 58%
See 1 more Smart Citation
“…3) have significantly colonized the lagoon's surroundings. The presence of these species in flooded environments has also been verified in other studies (Barros 2009;Xavier et al 2016;Rodrigues et al 2017). They are related to the anthropic disturbance that has been occurring in the flooded areas over the years and to characteristics such as propagule pressure, strong adaptation to low water depth, large seed production and resistance to environmental adversities (Havel et al 2015).…”
Section: Exotic Species In Lagoa Do São Bentosupporting
confidence: 58%
“…The study carried out in the municipalities of Recife, Santa Cruz do Capibaribe and Toritama, in the state of Pernambuco, which border the Rio Capibaribe, showed a result similar to that presented in this study. The authors compared different points on the riverbank and concluded that urbanization significantly influenced the floristic composition and structure of macrophyte communities (Xavier et al 2016).…”
Section: Floristic Analysis Of Aquatic Plantsmentioning
confidence: 99%
“…The inverse relation of Tem, NO 3 and/or PO 4 with O. cubense, L. helminthorrhiza or P. ferrugineum in the CCA called our attention, once these species are adjusted to waters rich in nitrogenate and phosphate nutrients (Mormul et al, 2010;Meyer and Franceschinelli, 2011;Moura Júnior et al, 2011;Tsheboeng et al, 2014;Xavier et al, 2016). It is possible that the limnological variables indicated by the forward selection have indirect relation with the species biomass in Post-WLF.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization promotes permanent changes in watersheds and stream channels (Paul & Meyer 2001); for example, stream channelization and soil impermeability lead to increases in substrate siltation and the homogenization of substrate sizes through an increase of sediments (Dala-Corte et al 2016, Montag et al 2019, promoting changes in channel depth, water velocity and the frequency and magnitude of floods. Together with nutrient enrichment, other contaminants and turbidity, these changes contribute to reducing macrophyte diversity (Paul & Meyer 2001, Xavier et al 2016. In agricultural streams, the impacts are related to water abstraction for crop irrigation, which reduces stream discharge and accelerates sedimentation rates (Sueyoshi et al 2016).…”
Section: Introductionmentioning
confidence: 99%